The Relationship Between Job Rotation Practices and Employee Career Development Among Production Workers in Japanese Companies in Malaysia - Mohd Zin, Md Lazim (2003)
This study investigated the relationship between job rotation practices and employee career development prospects among production workers of Japanese electronic companies in Malaysia. It examines the extent to which job rotation practices are significant to career development outcomes that are career progression, knowledge and skill and career management. A model of job rotation developed by Campion, Cheraskin and Stevens (1994) was used as the premise to test the linear relationship between job rotation and employee career development in the workplace. This is done by analyzing survey-based data sets particularly obtained from samples of 209 production workers in Japanese electronic manufacturing companies in Malaysia. The Pearson Correlation was used to measure the association between the variables and to test the research hypotheses. The results of the study found that there were significant correlation between job rotation practices and employee perception towards three career development outcomes, namely, career progression, knowledge and skill and job rotation benefits. Job rotation is considered as an important on-the job training and the emphasis on this practice should be made in order to ensure all employees participating in the job rotation could enjoy various experiences, knowledge and skills valuable to their career development in the future.